2021
DOI: 10.48550/arxiv.2109.11459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The TRAPPIST-1 Habitable Atmosphere Intercomparison (THAI). Part II: Moist Cases -- The Two Waterworlds

Denis E. Sergeev,
Thomas J. Fauchez,
Martin Turbet
et al.

Abstract: To identify promising exoplanets for atmospheric characterization and to make the best use of observational data, a thorough understanding of their atmospheres is needed. 3D general circulation models (GCMs) are one of the most comprehensive tools available for this task and will be used to interpret observations of temperate rocky exoplanets. Due to various parameterization choices made in GCMs, they can produce different results, even for the same planet. Employing four widely-used exoplanetary GCMs -ExoCAM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…LP 890-9 is the second-coolest star found to host planets after TRAPPIST-1. The seven terrestrial planets orbiting TRAPPIST-1 have garnered the interest of a broad community across very diverse scientific disciplines: planet formation and evolution (e.g., Ormel et al 2017;Coleman et al 2019;Raymond et al 2022), star-planet interactions (e.g., Bolmont et al 2017;O'Malley-James & Kaltenegger 2017;Dong et al 2018), multi-planet dynamics (e.g., Grimm et al 2018;Agol et al 2021;Teyssandier et al 2022), interior modelling (e.g., Dorn et al 2018;Barr et al 2018;Barth et al 2021), atmospheric observations (e.g., de Wit et al 2016Bourrier et al 2017;de Wit et al 2018) and modelling (e.g., Lustig-Yaeger et al 2019;Pidhorodetska et al 2020;Lin et al 2021), or climate predictions (e.g., Turbet et al 2018Turbet et al , 2021Sergeev et al 2021), among others. The discovery of the remarkable LP 890-9 system presented in this work offers another rare opportunity to study temperate terrestrial planets around our smallest and coolest neighbours.…”
Section: Discussionmentioning
confidence: 99%
“…LP 890-9 is the second-coolest star found to host planets after TRAPPIST-1. The seven terrestrial planets orbiting TRAPPIST-1 have garnered the interest of a broad community across very diverse scientific disciplines: planet formation and evolution (e.g., Ormel et al 2017;Coleman et al 2019;Raymond et al 2022), star-planet interactions (e.g., Bolmont et al 2017;O'Malley-James & Kaltenegger 2017;Dong et al 2018), multi-planet dynamics (e.g., Grimm et al 2018;Agol et al 2021;Teyssandier et al 2022), interior modelling (e.g., Dorn et al 2018;Barr et al 2018;Barth et al 2021), atmospheric observations (e.g., de Wit et al 2016Bourrier et al 2017;de Wit et al 2018) and modelling (e.g., Lustig-Yaeger et al 2019;Pidhorodetska et al 2020;Lin et al 2021), or climate predictions (e.g., Turbet et al 2018Turbet et al , 2021Sergeev et al 2021), among others. The discovery of the remarkable LP 890-9 system presented in this work offers another rare opportunity to study temperate terrestrial planets around our smallest and coolest neighbours.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have used GCMs, coupled with synthetic planetary spectrum generators, to simulate observations of transmission spectroscopy for transiting exoplanets (Arney et al 2017;Lines et al 2018;Boutle et al 2020;Suissa et al 2020;May et al 2021), enhancing the value of these models as an aid to interpreting observational data (Louden & Wheatley 2015;Brogi et al 2016). However, gaps in our understanding of the physics driving atmospheric phenomena on tidally locked planets, partly driven by differences in model structure and parameterizations (Sergeev et al 2020;Fauchez et al 2020;Sergeev et al 2021;Turbet et al 2021), may cause misinterpretations of atmospheric observations. Global 3D models of tidally locked planets exhibit an area of deep convection around the substellar point (Yang et al 2013;Kopparapu et al 2016;Hammond & Lewis 2021), leading to permanent cloud cover and heavy precipitation in this region (Yang et al 2013;Boutle et al 2017;Labonté & Merlis 2020;Sergeev et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Whether these parameterization schemes can be applied to exoplanet conditions is unknown, and different models employ different parameterization schemes. Recent model intercomparisons for tidally locked planets (Yang et al 2019b;Fauchez et al 2020;Sergeev et al 2021) have shown that there are large differences among the models in simulating the climate. Under a given stellar flux, a given greenhouse gas concentration, and the same boundary conditions (such as a uniform slab ocean at the surface), the simulated surface temperature differences in the global mean could be as large as 20-30 K. The underlying reasons are mainly due to cloud parameterization, the radiation calculation accuracy for water vapor, and differences in the relative humidity (which is associated with large-scale atmospheric circulation); the largest difference comes from clouds (Yang et al 2016(Yang et al , 2019b.…”
Section: Introductionmentioning
confidence: 99%